TI_GERICHTE 35.2023.25 vom 19. Juni 2023 , Corretta la decisione con la quale è stata dichiarata irricevibile l'opposizione - TI Tribunale d'appello (2023)
Corretta la decisione con la quale è stata dichiarata irricevibile l'opposizione